PENGETAHUAN, SIKAP, DAN FAKTOR PSIKOLOGIS BERHUBUNGAN DENGAN PERILAKU MEROKOK PADA PEGAWAI POLTEKKES KEMENKES JAKARTA III - Mohammad Ali Ali (Jurnal Ilmu dan Teknologi Kesehatan, 2014)
Public demands into a high quality of health examination with right, accurate and appropriate are increased. Hence, it is responsibility of health professional to provide better service. However, the number of health analyst workers called laboratorian have various diverse of educational background. In respon to providing high quality analysts, Polytechnic of Health Ministry of Health Jakarta III intends to identify its graduation who work in health services in Jakarta and surrounding areas. This study aims to evaluate the progress of Program D III at Health Analyst department as well as its development; to assess the need of user about health analysts education level; and to improve the performance of Health Analyst department. The study is designed as cross-sectional with the use of descriptive research / survey type. The target of population were the entire graduated of Health Analyst department. Data collection was conducted in the area of Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek) among alumni who work in hospital laboratories and 9 (nine) Clinics and Health Centers. Total number samples participated is 94 alumni. All data collected then was analyzed using SPSS. Learning experience in laboratory is the most important for alumni competence in the workplace, followed by learning experience in a community and hospital internships. It means there is association between education and the job attained. Professional certification is more important than academic achievement (IP), and participant expecting DIII program development into Bachelor level. " Tracer Study and labor Market Signal " encourage Health Analyst DIII Programme to improve Teaching Learning Process according to stakeholders needs Smoking is harmful. Therefore, many employees in the healthcare sector keep behave as smoker. The purpose of this study was to determine the correlation between knowledge, attitudes, and psychological factors on why people smoke. This survey is a cross-sectional study among 132 male staff at the Health Polytechnic Ministry of Health Jakarta III. Data analysis used was frequency distribution for univariate analysis, chi square test for bivariate analysis, and logistic regression for multivariate analysis. The result reveals that the number of respondents those have smoking habit is 45.5%, the majority of respondents have less knowledge (72.0%), those with positive attitude is 71.2%, and the number of psychological factors influence smoking practice is 58.3%. Bivariate analysis on variable knowledge, attitude, and psychological factors result in respectively data as follow: p=0.014 and OR=3.000, p = 0.016 and OR = 2.762, and p = 0.003 OR = 3.176. The dominant factor is well knowledge (OR = 6.658). Thus, we suggest that health promotion related quitting smoke should focus on increasing knowledge about bad effects of smoking.